Psikoedukasi rawat diri penyandang disabilitas pada pengurus forum keluarga disabilitas - Mohamad Ridhoddin Akbar (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Self-care is a basic thing that must be owned by every individual, but not every individual able to carry out self-care activities, especially for children with disabilities. Many families with disabilities experience difficulties due to the lack of information and the lack of soft skills related to disability self-care problems, thus hampering their function in managing and carrying out roles in the community. Psychoeducation is carried out with the aim of increasing the knowledge and skills of disability family forum (FKD) administrators regarding self-care for persons with disabilities. Psychoeducation was carried out in two stages with seven intervention sessions attended by 20 FKD members. The assessment used includes interviews, observations, pre-test and post-test sheets using multiple choice consisting of 10 questions. The results of providing psychoeducation showed a change in knowledge and an increase in skills in FKD management.The results of the post-test showed an increase in the knowledge of the administrators. A series of psychoeducational activities such as providing material, role play and discussions helped improve skills related to self-care for FKD administrators.